Open water swimming: swimmers` kinematical and neuromuscular characterisation in a 5 km swim - Conceição, A.; Marinho, D.; Stastny, J.; Gonçalves, C.; Freitas, J.; da Costa-Machado, R.; Louro, H. (Sports, 2025)
This study aimed to characterize and analyse the kinematic parameters and muscle activity of swimmers in open water swimming (OWS). Nine male swimmers (age: 25.4 ± 11.9 years; body mass: 75.9 ± 9.0 kg; height: 180.7 ± 6.7 cm; and arm span: 185.6 ± 10.3 cm) were evaluated in an open environment (lake), performing 5 m × 1000 m at maximum intensity, with a rest of 30 s every 1000 m. For kinematical analyses, the stroke rate (SR), swimming velocity (v), stroke length (SL), and stroke index (SI) were calculated. Surface EMG data were recorded in seven muscles—upper trapezius (UP); latissimus dorsi (LD); pectoralis major (PM); posterior deltoid (PD); anterior deltoid (AD); triceps brachii (TB); and biceps brachii (BB)—for the underwater and recovery phases of the stroke. SL (F = 3.41, p = 0.06, n2 = 0.30) and SI (F = 3.29, p = 0.08, n2 = 0.29) changed along the covered distances, and SR (F = 1.54, p = 0.24, n2 = 0.16) increased, especially in the last 1000 m (32.5 ± 3.0 cycles-min-1). AD was highly activated in recovery, showing statistical differences from the beginning (p = 0.01) to the end of the race (p = 0.03). The TB muscle was mostly recruited in the underwater phase, from the start (p = 0.01) to the finish (p = 0.03), showing a significant difference in each lap, with a large effect. LD showed significant differences in muscle activation, from 1000 m (p = 0.01) with a huge effect, to 5000 m (p = 0.01), with a large effect. These results suggested that the UT and AD muscles had higher activity in recovery than the underwater phase, and TB and LD were higher in the underwater phase.